A systematic investigation of the fragmentation pattern of two furanoheliangolide C‐8 stereoisomers using electrospray ionization mass spectrometry. (14th February 2014) - Sartori, Lucas Rossi; Vessecchi, Ricardo; Humpf, Hans‐Ulrich; Da Costa, Fernando Batista; Lopes, Norberto Peporine
<x xml:space="preserve">Abstract</x> RATIONALE Budlein A is a sesquiterpene lactone (STL) with some reported biological activities. Pre‐clinical studies to identify in vivo metabolites often employ hyphenated techniques such as liquid chromatography/tandem mass spectrometry (LC/MS/MS). It is also possible to use the fragmentation pattern obtained by Collision‐Induced Dissociation (CID) and Higher Energy Collision‐Induced Dissociation (HCD) to distinguish between the stereoisomers budlein A and centratherin. METHODS The experiments were carried out in the positive mode using four different spectrometers with an electrospray ionization (ESI) source: (a) Waters ACQUITY® TQD triple quadrupole mass spectrometer (QqQ), (b) AB Sciex API 4000 QTrap® (QqQ), (c) Bruker Daltonics micrOTOF™‐Q II (time‐of‐flight, QTOF), and (d) Thermo Scientific LTQ Orbitrap XL hybrid FTMS (Fourier transform mass spectrometer). Computational chemistry studies helped to identify the protonation sites. The B3LYP/6‐31G(d) model furnished the equilibrium geometries and energies. RESULTS The stereochemistry (α‐ or β‐orientation) of the centratherin and budlein A side‐chain esters influences the fragmentation pattern recorded on QqQ, QTOF, and Orbitrap‐HCD. On QqQ, centratherin releases the side chain, to generate the m/z 275 fragment ion, whereas budlein A gives the m/z 83 fragment ion. On QTOF and Orbitrap‐HCD, only budlein A affords the m/z 293 and 83 fragment ions, respectively. CONCLUSIONS The data suggest that proton migration governs the fragmentation pathways under α‐ or β‐orientation. The difference in the QqQ, QTOF, and Orbitrap‐HCD spectral profiles of each isomer can help to distinguish between centratherin and budlein A using MS/MS, which becomes an alternative to nuclear magnetic resonance (NMR) analysis. Copyright © 2014 John Wiley & Sons, Ltd.